Comparative study of static and cyclic fatigue of ZrB2-SiC ceramic composites. Issue 4 (April 2018) - Lugovy, M.; Orlovskaya, N.; Slyunyayev, V.; Mitrentsis, E.; Neumann, M.; Aneziris, C.G.; Jelitto, H.; Schneider, G.A.; Kuebler, J.
Abstract: Room temperature static and cyclic fatigue of ZrB2 -32 vol% SiC and ZrB2 -45 vol% SiC particulate ceramic composites has been studied. It was established that the presence of grain bridging plays an important role in the lifetime and time dependent mechanical performance of ZrB2 -SiC composites. It was also established that the cohesive strength of grain boundaries of the composites was a determining factor if grain bridging would occur during crack growth, as the grain boundaries strength would determine the pathway of the moving crack. Grain bridging was limited in ZrB2 -32 vol% SiC leading to the absence of a cyclic fatigue effect, while grain bridging indeed occurred in ZrB2 -45 vol%SiC contributing to a cyclic fatigue effect which limits the lifetime of the composite. Such differences were responsible for the occurrence of R-curve behavior in ZrB2 -SiC ceramic composites.